Substituting systolic blood pressure with shock index in the National Trauma Triage Protocol. Issue 6 (December 2016) - Haider, Ansab A.; Azim, Asad; Rhee, Peter; Kulvatunyou, Narong; Ibraheem, Kareem; Tang, Andrew; O'Keeffe, Terence; Iftikhar, Hajira; Vercruysse, Gary; Joseph, Bellal
Abstract : INTRODUCTION: The National Trauma Triage Protocol (NTTP) is an algorithm that guides emergency medical services providers through four decision steps to identify the patients that would benefit from trauma center care. The NTTP defines a systolic blood pressure (SBP) of less than 90 mm Hg as one of the criteria for trauma center need. The aim of our study was to determine the impact of substituting SBP of less than 90 mm Hg with shock index (SI) on triage performance. METHODS: A 2-year (2011–2012) retrospective analysis of all trauma patients 18 years or older in the National Trauma Databank was performed. Transferred patients, patients dead on arrival, and those with missing data were excluded. Our outcome measure was trauma center need defined by Injury Severity Score greater than 15, need for emergent operation, death in the emergency department, and intensive care unit stay of more than 1 day. Area under the characteristic curve and triage characteristics were compared between SBP of less than 90 mm Hg and SI of more than 1.0. Logistic regression analysis was performed to compare the mortality between patients triaged under current protocol of SBP of less than 90 mm Hg and patients triaged using the new defined protocol (SI >1.0). RESULTS: A total of 505, 296 patients were included. Compared with SBP of less than 90 mm Hg, SI of more than 1.0 had a higher sensitivity (44.4% vs. 41.7%) but lower specificity (80.2% vs. 82.4%). The area under the curve was significantly higher for SI of more than 1.0 (0.623 [95% confidence interval, 0.622–.625] vs. 0.620 [95% confidence interval, 0.619–0.622]). Substituting SBP of less than 90 mm Hg with SI of more than 1.0 resulted in a decrease in undertriage rate of 30, 233 patients (5.9%) but an increase in overtriage of only 6, 386 patients (1.3%). CONCLUSION: Substituting the current criterion of SBP of less than 90 mm Hg in the NTTP with an SI of more than 1.0 results in significant reduction in undertriage rate without causing large increase in overtriage. Because of simplicity of use, better discrimination power, and minimal effect on overtriage rates, future studies should consider exploring the possibility of replacing the current SBP of less than 90 mm Hg criterion with SI of more than 1.0 in the NTTP. LEVEL OF EVIDENCE: Prognostic study, level III; therapeutic study, level IV.